Radiation therapy attenuates lymphatic vessel repair by reducing VEGFR-3 signalling - Pillay, Vinochani; Shukla, Lipi; Herle, Prad; Maciburko, Simon; Bandara, Nadeeka; Reid, Isabella; Morgan, Steven; Yuan, Yinan; Luu, Jennii; Cowley, Karla J.; Ramm, Susanne; Simpson, Kaylene J.; et al. (Frontiers in Pharmacology, 2023)
Introduction: Surgery and radiotherapy are key cancer treatments and the leading causes of damage to the lymphatics, a vascular network critical to fluid homeostasis and immunity. The clinical manifestation of this damage constitutes a devastating side-effect of cancer treatment, known as lymphoedema. Lymphoedema is a chronic condition evolving from the accumulation of interstitial fluid due to impaired drainage via the lymphatics and is recognised to contribute significant morbidity to patients who survive their cancer. Nevertheless, the molecular mechanisms underlying the damage inflicted on lymphatic vessels, and particularly the lymphatic endothelial cells (LEC) that constitute them, by these treatment modalities, remain poorly understood. Methods: We used a combination of cell based assays, biochemistry and animal models of lymphatic injury to examine the molecular mechanisms behind LEC injury and the subsequent effects on lymphatic vessels, particularly the role of the VEGF-C/VEGF-D/VEGFR-3 lymphangiogenic signalling pathway, in lymphatic injury underpinning the development of lymphoedema. Results: We demonstrate that radiotherapy selectively impairs key LEC functions needed for new lymphatic vessel growth (lymphangiogenesis). This effect is mediated by attenuation of VEGFR-3 signalling and downstream signalling cascades. VEGFR-3 protein levels were downregulated in LEC that were exposed to radiation, and LEC were therefore selectively less responsive to VEGF-C and VEGF-D. These findings were validated in our animal models of radiation and surgical injury. Discussion: Our data provide mechanistic insight into injury sustained by LEC and lymphatics during surgical and radiotherapy cancer treatments and underscore the need for alternative non-VEGF-C/VEGFR-3-based therapies to treat lymphoedema.